2020
DOI: 10.1080/1354750x.2020.1829056
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity Troponin-T for prediction of adverse events in patients with COVID-19

Abstract: Background: High sensitivity troponin-T (hs-TnT) has been associated with mortality in patients hospitalized with COVID-19. We aimed to determine if hs-TnT levels and their timing are independent predictors of adverse events in these patients. Design: Retrospective chart review was performed for all patients hospitalized at our institution between March 23 rd and April 13 th , 2020 who were found to be COVID-19-positive. Clinical, demographic, and laboratory variables including initial and peak hs-TnT were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
4
10
1
1
Order By: Relevance
“…We observed higher values among the non-survivor group than the survivor group, which is consistent with recent studies indicating derangement of liver function tests associated with severe COVID-19 [ 45 ]. Further, the high troponin level was associated with increased mortality, consistent with the findings of recent studies that showed that higher troponin was associated with a longer hospital stay and death [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…We observed higher values among the non-survivor group than the survivor group, which is consistent with recent studies indicating derangement of liver function tests associated with severe COVID-19 [ 45 ]. Further, the high troponin level was associated with increased mortality, consistent with the findings of recent studies that showed that higher troponin was associated with a longer hospital stay and death [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…Many critically ill COVID-19 patients demonstrate concomitant elevations in acute phase reactants such as procalcitonin (PCT), serum ferritin, erythrocyte sedimentation rate (ESR), CRP, interleukin (IL)-6 and the natriuretic peptides 23 , supporting the main reason of a cardio-inflammatory response. It has been reported that elevated cTn served as a marker of risk of future adverse events based on the current severity of the infectious disease and inflammatory process, but not necessarily as a marker of hard cardiovascular outcomes 24 . In clinical practice, however, it is challenging to determine whether elevated cTnI levels are caused by direct COVID-19 infection or by the progress of these preexisting medical conditions 25 .…”
Section: Discussionmentioning
confidence: 99%
“…We used nationwide data and had a large sample size, which emphasizes the prevalence and prognostic role of cTn in COVID-19. We used the only cTn values at admission; however, the serial measurements of cTn during hospitalization might also be an important marker of severity and prognosis despite the normal initial level at admission 5 , 12 , 15 , 16 , 24 , 29 . The other limitation of our study was the analytic accuracy of the prognosticative value of cTn, given the different assays used at each hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Given increasing evidence for cardiovascular manifestations of COVID-19, and the increasing role of bedside focused cardiac ultrasound (FoCUS) in clinical management, there may be utility in performing a focused bedside ECHO among patients with COVID-19, especially in the critically ill [3][4][5]. Although performing an ECHO solely based on troponin elevation is not recommended, there is an increasing body of data suggesting that elevated troponin (>99 th percentile on admission) is an important predictor of mortality and length of hospital stay in patients with COVID-19 [6][7][8][9][10]. Similarly, NT-ProBNP has also been found to be elevated among a significant number of patients with COVID-19 and is an important predictor of mortality [11].…”
Section: Indications For Echocardiography In Covid-19 Patientsmentioning
confidence: 99%